2014
DOI: 10.1089/zeb.2013.0969
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Social Behavior in Zebrafish: Live Versus Computer Animated Fish as Stimuli

Abstract: The zebrafish offers an excellent compromise between system complexity and practical simplicity and has been suggested as a translational research tool for the analysis of human brain disorders associated with abnormalities of social behavior. Unlike laboratory rodents zebrafish are diurnal, thus visual cues may be easily utilized in the analysis of their behavior and brain function. Visual cues, including the sight of conspecifics, have been employed to induce social behavior in zebrafish. However, the method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
93
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 88 publications
(99 citation statements)
references
References 50 publications
3
93
1
2
Order By: Relevance
“…Further advantage of inducing and measuring shoaling in this manner is that one can monitor the behaviour of a single subject, which allows identification of mutation or drug induced changes more precisely than what may be achieved when one has to monitor the complex interactions among multiple subjects, as is the case in live shoals. movement, and cues other than visual are not necessary to induce maximal shoaling responses, as defined by the distance between test fish and the stimulus, in zebrafish (Qin et al, 2014). In summary, presentation of animated conspecifics is a reliable, and consistently controllable stimulus that induces a robust shoaling response that lasts as long as the stimulus is presented.…”
Section: Induction and Quantification Of Shoalingmentioning
confidence: 92%
See 1 more Smart Citation
“…Further advantage of inducing and measuring shoaling in this manner is that one can monitor the behaviour of a single subject, which allows identification of mutation or drug induced changes more precisely than what may be achieved when one has to monitor the complex interactions among multiple subjects, as is the case in live shoals. movement, and cues other than visual are not necessary to induce maximal shoaling responses, as defined by the distance between test fish and the stimulus, in zebrafish (Qin et al, 2014). In summary, presentation of animated conspecifics is a reliable, and consistently controllable stimulus that induces a robust shoaling response that lasts as long as the stimulus is presented.…”
Section: Induction and Quantification Of Shoalingmentioning
confidence: 92%
“…Thus, as long as the same number of shoal members are used in experimental analyses, interindividual distance is the recommended measure. Irrespective of which measure one uses, the problem with using live shoals to induce and measure shoaling is that behaviour of the shoal is The second way to induce and evaluate shoaling responses in zebrafish is to present social stimuli (live, or computer animated images of, conspecifics) to a single experimental subject (Saverino & Gerlai, 2008;Fernandes & Gerlai, 2009;Qin et al, 2014). A single experimental subject in a novel test tank is highly motivated to join the shoal, thus upon presentation of the social stimuli, it usually approaches the stimuli and stays in close proximity of the stimuli.…”
Section: Induction and Quantification Of Shoalingmentioning
confidence: 99%
“…The second way to induce and evaluate shoaling responses in zebrafish is to present social stimuli (live, or computer animated images of, conspecifics) to a single experimental subject (Saverino & Gerlai, 2008;Fernandes & Gerlai, 2009;Qin et al, 2014). A single experimental subject in a novel test tank is highly motivated to join the shoal, thus upon presentation of the social stimuli, it usually approaches the stimuli and stays in close proximity of the stimuli.…”
Section: Induction and Quantification Of Shoalingmentioning
confidence: 99%
“…Further using this method, one can monitor the behaviour of a single subject, which allows identification of mutation or drug induced changes more precisely than when measuring interactions among multiple shoal members. stimulus fish video-taped and the recording replayed (only visual cues available, stimulus fish not interacting, but move in 3D), computer animated images (only visual cues available, stimulus fish not interacting, and move in 2D) using two different software applications were presented (Qin et al, 2014). The results indicated that experimental zebrafish responded equally well to all these stimuli, i.e., interaction with conspecifics, 3D movement, and cues other than visual were found not necessary to induce maximal shoaling responses, as defined by the distance between test fish and the stimulus, in zebrafish (Qin et al, 2014).…”
Section: Induction and Quantification Of Shoalingmentioning
confidence: 99%
See 1 more Smart Citation